2015
DOI: 10.1515/ata-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating The Effectiveness Of Production Process Using Pareto Analysis

Abstract: The aim of this paper is to present the possibilities of using the Pareto method in evaluating the effectiveness of machine production processes. The paper deals with the production process of material cutting using progressive technology and subsequent evaluation of its effectiveness and quality. In the production process, we have used the method of material cutting by abrasive water jet. The Pareto analysis was used for eliminating the shortcomings in the quality of the final part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the FFD experiments, the wide range of the set factor levels resulted in the target peaks not reaching the baseline separation under most conditions, and some of the experimental results were zero, which was not conducive to the analysis of factor effects with missing information. CCD was the most commonly used RSM experiment, which can obtain a large amount of information about experimental variables and experimental errors with a minimum number of test cycles [30]. The experimental factors and the levels of the CCD experiment are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the FFD experiments, the wide range of the set factor levels resulted in the target peaks not reaching the baseline separation under most conditions, and some of the experimental results were zero, which was not conducive to the analysis of factor effects with missing information. CCD was the most commonly used RSM experiment, which can obtain a large amount of information about experimental variables and experimental errors with a minimum number of test cycles [30]. The experimental factors and the levels of the CCD experiment are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…[25,26] The value of Z1 in simplex optimization provides a solution for optimizing the farmers' profit by an average price. [27,28,29] The value of Z2 in simplex optimization provides a production solution based on the average amount of consumption. In this case, Pareto makes a representative solution philosophy in deciding production and optimization criteria Z1 and Z2 for medium-quality and super-quality rice in the form of graphs.…”
Section: 𝑥 ∈ 𝑆mentioning
confidence: 99%
“…Heena Sharma and Dr. N.M Suri (2017) categorized the defects in LV Electrical Panels during in-process and at final stage using Pareto analysis and found that 27% rejections are due to poor welding. Polak et al (2015) evaluated the cut quality of Hydro abrasive metal cutting by Pareto method and Abhay et al (2014) studied the reasons for rejection of forging of cam shaft gear in a leading forging industry and found that furnace issues and die crack are the predominant ones. Joshi and Jugulkar (2014) analysed the reasons for rejection of castings from an industry using Pareto analysis and found that flash, mould shifting and buckling are the major factors contributing for rejections.…”
Section: Literature Reviewmentioning
confidence: 99%